White spot lesions during multibracket appliance treatment : a challenge for clinical excellence - Enaia, Mahmoud; Justus Liebig University Giessen (My University, 2010)
The present study aimed to investigate the incidence and further course of White Spot Lesions (WSL) during and after multibrackets appliance (MB) treatment. All former MB-patients finishing orthodontic treatment at the University of Giessen between 1996 and 2006 were screened. The first 400 patients (168 male, 232 female) meeting the in-clusion criteria - all upper front teeth (UFT) fully erupted and visible on before treatment photographs, no fillings or structural abnormalities, duration MB treatment greater-than-or-equal 1 year, retention period greater-than-or-equal 1 year - were selected. The average age of the patients was 13.7 years (SD 3.5) and the average MB treatment time 1.9 years (SD 3.6). A modification of the White Spot Index by Gorelick et al. (1982) was used to evaluate the labial surface of the four front teeth in the upper incisor area on intra-oral photos before (T0), after treatment (T1) and after the end of retention (T2). The results revealed the following: Before treatment 32.3% of the patients exhibited WSL on 19.7% of the UFT. After MB treatment 73.5% of the patients and 57.4% of the UFT presented WSL. The incidence of WSL during MB treatment amounted to 60.9% of the patients. The majority of the UFT (41.2%) had mild lesions while the remaining UFT were af-fected severely with (3.8%) or without (12.4%) cavitations at T1. Only 26.5% of the patients were free of WSL both at T0 and at T1. After the retention phase the majority of the lesions (68.4%) were improved, 20.7% were unchanged and 10.9% had worsened. Male WSL-patients tended to show more severe WSL than females. There was a tendency for an increased WSL development during the adolescent com-pared to pre- and post-adolescent age groups. It was concluded, that using only general prophylactic measures, new WSL developing on the UFT during MB treatment remain to be a frequent undesired side-effect affecting 60.9% of the patients counteracting our efforts for clinical excellence.

Ziel der vorliegenden Arbeit war es, die Inzidenz und weitere Entwicklung von White Spot Läsionen (WSL) während Multibracket-Behandlung (MB) zu untersuchen.Aus allen Patienten, die zwischen 1996 und 2006 eine MB-Behandlung an der Universität Gießen abgeschlossen hatten, wurden die ersten 400 Patienten (168 männlich, 232 weiblich), die die Einschlußkriterien erfüllten ausgewählt. Einschlußkriterien: alle vier oberen Frontzähne (OK-FZ) vor der Behandlung vollständig durchgebrochen, keine Füllungen oder Struktur-Abnormitäten, MB-Behandlungszeit größer/gleich 1 Jahr, Retentionsphase größer/gleich 1 Jahr. Das durchschnittliche Alter der Patienten vor Behandlung betrug 13,7 Jahre (SD 3,5) und die durchschnittliche MB-Behandlungszeit 1,9 Jahre (SD 3,6). Eine Modifizierung des WSL-Index nach Gorelick et al. (1982) wurde verwendet, um die labiale Oberfläche der OK-FZ anhand intraoraler Fotos vor Behandlung (T0), nach Behandlung (T1) und am Ende der Retentionsphase (T2) zu bewerten. Die Studie führte zu den nachfolgend gelisteten Ergebnissen: Vor der Behandlung wiesen 32,3% der Patienten bzw. 19,7% der OK-FZ WSL auf. Nach der MB-Behandlung hatten 73,5% der Patienten bzw. 57,4% der OK-FZ WSL. Die WSL-Inzidenz während MB-Behandlung betrug 60,9% der Patienten. Die Mehrzahl der OK-FZ (41,2%) hatten bei T1 leichte WSL, während ein hoher Schweregrad mit/ohne Kavitationen bei 3,8% respektive 12,4% der OK-FZ vorlag. Nur 26,5% der Patienten hatten sowohl bei T0 als auch bei T1 keine WSL. Nach der Retentionsphase hatten sich die Mehrzahl der Läsionen (68,4%) verbessert, 20,7% blieben unverändert und 10,9% verschlechterten sich. Männliche WSL-Pateinten zeigten mehr schwergradige WSL als die weiblichen. Tendenziell entwickelten adoleszente Patienten mehr WSL als prä- und postadoleszente Individuen.Trotz verbesserter allgemeiner prophylaktischer Maßnahmen bleiben WSL, die sich während der MB-Behandlung an den oberen Frontzähnen entwickeln, eine häufige unerwünschte Nebenwirkung die 60.9% der Patienten betrifft und somit unserem Streben nach klinischer Ex-zellenz widerspricht.
Entkalkung während Multibracket-Behandlung : ein ungelöstes Problem
Keywords: Entkalkung; Multibracket-Behandlung; multibracket; White spot lesions; ddc:610